2023
DOI: 10.20944/preprints202306.2154.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distribution of HPV Types in Tumor Tissue from Women with Cervical Cancer in Norway

Abstract: Background: Understanding the distribution of HPV types in cervical cancer cases is crucial for evaluating the effectiveness of HPV screening and vaccination in reducing cervical cancer burden. This study aimed to assess genotype prevalence among 178 cervical cancer cases detected during a 20-year screening period in Northern Norway and compare the potential efficacy of HPV vaccines in preventing cervical cancer. Methods: A total of 181 formalin-fixed paraffin-embedded (FFPE) tissue samples from women diagnose… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…A Norwegian study aligns with these findings, as HPV 16, 18, and 45 emerged as the predominant HPV types detected in cervical cancer cases, predominantly among women aged 35–40. Conversely, other oncogenic HPV types, including 31, 33, 35, 39, 52, 58, and 73, displayed a higher prevalence among older age groups [ 19 ]. Notably, two cross-sectional studies investigating HPV distribution in European ICC cases also reported a significant association between young age and HPV 16-, 18-, and 45-positive cervical cancer cases [ 20 ], bolstering our own findings where the mean age for these three types ranged approximately from 44 to 45 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Norwegian study aligns with these findings, as HPV 16, 18, and 45 emerged as the predominant HPV types detected in cervical cancer cases, predominantly among women aged 35–40. Conversely, other oncogenic HPV types, including 31, 33, 35, 39, 52, 58, and 73, displayed a higher prevalence among older age groups [ 19 ]. Notably, two cross-sectional studies investigating HPV distribution in European ICC cases also reported a significant association between young age and HPV 16-, 18-, and 45-positive cervical cancer cases [ 20 ], bolstering our own findings where the mean age for these three types ranged approximately from 44 to 45 years.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of the remaining eight HPV types covered by most screening tests only marginally increased the prevalence by 1.5% [ 21 ]. Similarly, a Norwegian study reported that the eight additional types were detected in only 1.4% of screen-detected cancers, while the majority (93.0% or 66 out of 71 cases) were caused by HPV types 16, 18, 31, 33, and 45 [ 19 ]. In Europe, it has been reported that the majority of cervical cancer cases are caused by five high-risk HPV types, namely HPV 16, 18, 31, 33, and 45 [ 22 ].…”
Section: Discussionmentioning
confidence: 99%